Application of TPACK (Tecnological Pedagogical Content Knowledge) in Accounting Subjects at Vocational High School (SMK) Batik 1 Surakarta - Indri Septi Guntari; Surya Jatmika (Cetta: Jurnal Ilmu Pendidikan, 2023)
The purpose of this study was to determine the application of Technological Pedagogical Content Knowledge (TPACK) at SMK Batik 1 Surakarta. The main components of TPACK consist of Pedagogical Knowledge (PK), Content Knowledge (CK) and Technology Knowledge (TK). The type of method used in this research is case study research with a qualitative approach. The subjects of this research are accounting subject teachers, and three students from class XI accounting. Data collection techniques were conducted through interviews, observation, and documentation. Data analysis techniques were carried out through reduction, presentation, and conclusion drawing. The results showed the application of TPACK using learning media: (1) Videos made using applications or adjusting to accounting subjects. (2) The application of learning with e-learning (google classroom) starting during the COVID-19 pandemic was used during learning to deliver Flipbook teaching materials or Quizizz in the form of information technology in the form of a website that can be accessed anywhere. Based on the research conducted, there are several researchers who also discuss or review this research.